The astructural bias charge myth or reality? - Musolf, Gil Richard, 1951- (Studies in symbolic interaction ;, 2016)
The charge that symbolic interactionism (SI) is impaired by an astructural bias orbits around a number of sociology's core concerns: structure and agency, methodological individualism and methodological holism, the micro-macro link, the proper procedures to conduct research and when to state and how to test hypotheses and, whether interactionism can address structural concerns such as class, race, gender, power, and oppression. The Astructural Bias: Myth or Reality constitutes a collection of outstanding essays by scholars who address the concern of an astructural bias. Chapters explore the nature of social structure and SI's effectiveness in using the concept. This volume is beneficial for contemporary interactionists and their critics, social theorists, and all students of sociology who are interested in assessing the ability of SI to fully address the grave social circumstances and social problems of an increasingly precarious and dangerous world.